Multimodal MRI Approach for Differentiating Ring-Enhancing Brain Lesions: Integration of DWI and MR Spectroscopy - B, Akshay.; Kakileti, Bharath; M, Abhilash.; Varalakshmi, Gali; Khambhampati, Tharunkrishna; Srujan, S.; T, Abhishekratan. (Journal of Neonatal Surgery, 2025)
Background: Ring-enhancing brain lesions present a diagnostic challenge, as they can be caused by various pathologies, including neoplastic, infectious, and inflammatory conditions. Conventional MRI alone often lacks specificity in differentiating these lesions. Objective: This study aims to evaluate the role of advanced MRI techniques—Diffusion-Weighted Imaging (DWI) and Magnetic Resonance Spectroscopy (MRS)—in conjunction with conventional MRI for the characterization of ring-enhancing brain lesions. Methods: A cohort of patients with radiologically confirmed ring-enhancing lesions underwent MRI, including DWI and MRS. Apparent Diffusion Coefficient (ADC) values and metabolic spectra were analyzed to distinguish between neoplastic and non-neoplastic lesions. Correlation of imaging findings with histopathology or clinical follow-up was performed to assess diagnostic accuracy. Results: DWI and ADC mapping provided crucial insights into lesion cellularity, aiding in the differentiation between abscesses and tumors. MRS findings, including choline/N-acetylaspartate (Cho/NAA) and choline/creatine (Cho/Cr) ratios, further enhanced specificity in distinguishing malignant from benign lesions. The combined approach significantly improved diagnostic accuracy compared to conventional MRI alone. Conclusion: Integrating DWI and MRS with conventional MRI enhances the diagnostic capabil ity in assessing ring-enhancing brain lesions. This multimodal approach offers improved differentiation of infectious, inflammatory, and neoplastic conditions, thereby guiding appropriate clinical management.